KONTRIBUSI JURNAL TERBITAN UNIVERSITAS NEGERI MALANG SEBAGAI MEDIA KOMUNIKASI ILMIAH DALAM MENUMBUHKAN PENGGUNAAN LITERATUR PRIMER BAGI MAHASISWA STRATA 1 DAN 2 UNIVERSITAS NEGERI MALANG” - H. Sokhibul Ansor; Setiawan Setiawan (Perpustakaan Nasional RI, 2016)
This study sought to find the contribution of the journal published by the State University of Malang (SUM) as a scientific communication media to enhance the use of primary literature among graduate and undergraduate students of SUM. Theory used to describe the mechanism of the correlational concept was model use and gratification theory which emphasizes on how the journal published by SUM meets both personal and social needs in achieving certain goals. This study used descriptive method. Data was gathered through observations, interviews, and questionnaires carried out to 30 patrons who used serial and selected information services in SUM library. The patrons consisted of 18 undergraduate students and 12 graduate students. Results showed that in general the journal has contributed to meet the needs of the patrons in primary literature. It was also discovered that the SUM journal has not been published regularly.